Low voltage operating InGaZnO4 thin film transistors using high-k MgO-Ba0.6Sr0.4TiO3 composite gate dielectric on plastic substrate - Kim, Dong Hun; Cho, Nam Gyu; Kim, Ho-Gi; Kim, Hyun-Suk; Hong, Jae-Min; Kim, Il-Doo (AMER INST PHYSICS, 2008)
The authors report on the dielectric and leakage current properties of room temperature grown MgO-Ba0.6Sr0.4TiO3 (MgO-BST) composite thin films to be utilized InGaZnO4 thin films transistors (TFTs) fabricated on a polyethylene terephthalate (PET) substrate. The InGaZnO4 TFTs with MgO-BST gate dielectrics exhibited low operation voltage of 4 V, high on/off current ratio of 4.13x10(6), and high field effect mobility of 10.86 cm(2)/V s. These results verify that a room temperature grown MgO-BST gate dielectric is a good candidate for producing high performance InGaZnO4 TFTs on plastic substrates. (C) 2008 American Institute of Physics.
Keywords: AMORPHOUS OXIDE SEMICONDUCTORS